High-energy fixed-angle meson scattering and the constituent counting rule in holographic QCD - Adi Armoni; Bartosz Pyszkowski; Shigeki Sugimoto; Dorin Weissman (Journal of High Energy Physics)
Abstract We investigate the high-energy fixed-angle scattering of pions and ρ-mesons in a bottom-up holographic QCD model. To this end, we generalise the approach of Polchinski and Strassler [1] to write an ansatz for meson scattering amplitudes based on superstring scattering amplitudes in asymptotically AdS space. We demonstrate that our generalisation of the Polchinski-Strassler proposal is necessary to describe ρ-meson scattering consistently with the Nambu-Goldstone boson equivalence theorem. Our results for pion and ρ-meson scattering amplitudes are in agreement with the constituent counting rule found in QCD. Moreover, our proposal for 2-to-2 scattering amplitudes provides a method for computing scattering angle dependence.